Research Path on Climate Change Accounting - Uula, Mimma Maripatul (Accounting and Sustainability, 2024)
This study aims to see the development of research on the topic of "Climate Change Accounting" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Climate Change Accounting" which comes from the database Dimension with a total of 181 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "research development Climate Change Accounting" in the world. The results of the study found that there are 4 clusters with the most used words are impact, distribution, species, area, mission, accounting, condition, factor, ecosystem, and temperature. Then, the research path topics related to Climate Change Accounting are Carbon Accounting and Financial Reporting, Natural Resource Accounting and Climate Change, Future Climate Scenarios in Accounting, and Exposure to Climate Risks Accounting.